Skills and strategies for teaching information literacy in the curriculum of the discipline of library science - Martínez Rider, Dra Rosa María (2013)
Information literacy is a tool for development for citizens and the social sectors. The librarian is the professional that promotes the development of skills for the democratic exercise of information use for decision-making and problems solving. This raises a curriculum design based on competences and teaching strategies different to the traditional ones that are carried out in the study plans based on the models of knowledge.